Effect of Dalmavital and Ovulik Plus on conception rate in Ovsynch synchronized Nili-Ravi buf- faloes - Muhammad Tayyab Khan; Muhammad Muzammal Niaz; Ghulam Shabbir Khan (Revista Científica)
Nili-Ravi buffalo are known as the “Black Gold of Pakistan”. It is the most prized dairy animal in Pakistan. Silent estrus and shy behavior are among the main causes of poor reproductive efficiency in buffalo, leading to prolonged calving intervals. Ovulik Plus® is a supplementary mixture for stimulating fertility. It provides energy, eliminates the deficiency of ß-carotene, as well as giving a rich source of vitamins and microelements to elevate reproductive efficiency. Dalmavital® is another product that contains ß-carotene and acts as an antioxidant source. Our objective was to compare the impact of these supplements in enhancing conception rates of Ovsynch synchronized Nili-Ravi buffaloes. For this purpose, buffaloes (n=45) with healthy reproductive tract, BCS (2.5-3.5), and mixed parity (2-3) were enrolled into three groups: G1: Ovsynch + Dalmavital (IM), G2: Ovsynch + Ovulik (PO) and G3: Ovsynch without supplementation as control. For the Ovsynch protocol, buffaloes were administered with 2ml (IM) injection of GnRH (Lecirelin acetate 25μg/ml) at day 0, followed by 2ml (IM) injection of PGF2α (D-cloprostenol 75μg/ml) at day 7. Finally, 2ml GnRH was injected (IM) at day 9. Dalmavital was injected (IM) at the rate of 1ml/40kg body weight at day 5 in G1, and Ovulik Plus was offered by drenching gun just after 1st AI as a single dose of 1000 g/ buffalo. Double inseminations were performed at standing estrus, morning and evening, at intervals of 12 and 24 h after the last GnRH injection. Pregnancies were confirmed through ultrasonography at day 40. Data were analyzed through the Chi-Square test and Binary Logistic Regression model using SPSS. Results revealed no difference (p>0.05) in estrus response among all groups. Conception rates were higher (p<0.05) in G2 compared to G3 (60% vs. 46.66%, respectively). However, there was  no difference (p >0.05) in conception rates of G1 and G2 (53.33% vs. 60%, respectively). In conclusion, Ovulik Plus per oral was superior to intramuscular administration of Dalmavital in improving conception rates of Ovsynch synchronized Nili-Ravi buffaloes.